PENGARUH USER-RELATED FACTORS TERHADAP KUALITAS HASIL PENGEMBANGAN SISTEM INFORMASI - EKO ARIEF SUDARYONO; AHMADI TRI HUTOMO; DODDY SETIAWAN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2007)
This research aims to test the effect of user related factors on the quality of information system development result, we analyze four factors of user-related: user participation as independent variable and user-developer communication, user influence, user conflict as moderating variables. The samples of this research consist of managers from Sleman, Surakarta, Karanganyar, and Sukoharjo. We use Moderated Regression Analysis (MRA) to test the hypothesis. The results of this research show that user-developer communication as moderating variables on the relationship between user participation and the quality of information system development result. While user influence and user conflict does not moderate these relationship.